Impulsivity and craving in subjects with opioid use disorder on methadone maintenance treatment. (1st February 2021) - Li, Jun; Weidacker, Kathrin; Mandali, Alekhya; Zhang, Yingying; Whiteford, Seb; Ren, Qihuan; Zhou, Zhirong; Zhou, Huijing; Jiang, Haifeng; Du, Jiang; Zhang, Chencheng; Sun, Bomin; et al.
Highlights: Cognitive functions under methadone maintenance treatment (MMT) were assessed. Delay discounting increases, but other forms of impulsivity are normal in patients. Impaired associative learning in MMT patients is related to depression and anxiety symptoms. Increased delay discounting and craving are correlated with impulsive personality scores. Cue-induced drug craving in MMT patients is modulated by withdrawal symptoms. Abstract: Background: Methadone maintenance treatment (MMT) is effective in decreasing opioid use or facilitating abstinence. Previous studies using small opioid use disorder samples suggest that cognitive impairments including impulsivity and executive functions may partially improve on MMT, but a range of deficits may persist. However, systematic assessments with larger samples are needed to confirm the profile of cognitive functions on MMT. Methods: We assessed four types of impulsivity (delay discounting, reflection impulsivity, risk taking and motoric impulsivity), executive functioning (spatial working memory, paired associative learning and strategic planning) and drug cue-induced craving in a relatively large population (115 MMT patients, 115 healthy controls). The relationships between impulsivity, drug cue-induced craving and addiction-related variables were also assessed. Results: Delay discounting, as well as drug cue-induced craving was increased in patients, while motoric impulsivity was lower than in controls. Paired associative learning was additionally impaired, which was explained by increased depression and anxiety levels in patients. Within the MMT group, the delay discounting and drug-cue induced craving scores were positively correlated with self-reported urgency, but unrelated to methadone dosage, duration on methadone, withdrawal symptoms, or presence of nicotine dependence. Conclusions: Our findings highlight increased delay discounting and cue-induced craving in MMT patients suggesting a potential role for trait effects in delay discounting. Although previous smaller studies have shown impaired executive function, in our large sample size on chronic MMT we only observed impaired associative learning related to depressive and anxiety symptoms highlighting a role for managing comorbid symptoms to further optimize cognitive function.